2019
DOI: 10.1016/j.pocean.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variability of sea ice and phytoplankton biomarker flux in the Chukchi sea (western Arctic Ocean)

Abstract: Sediment traps were deployed at 870 m water-depth from August 2008 to September at station DM in the Chukchi Sea (western Arctic Ocean) in an area covered by sea ice in winter to determine seasonal fluxes of HBIs and phytoplankton sterols in order to improve our understanding of sea ice proxies. HBI-III fluxes and P III IP 25 are for the first time documented in the Arctic Ocean to evaluate their significance for paleoclimate reconstructions. Highest mass fluxes were found from mid-July 2009 to September 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 88 publications
8
42
0
Order By: Relevance
“…Peak IP 25 fluxes during early July 2016 (1331 ng m -2 d -1 ), coincided with the largest flux of the diatom group Gyrosigma/Pleurosigma/Haslea (Fig 2D), which account for~1% of the relative abundance of major diatom taxa groups [49]. This value is higher than maximum values observed in August 2008 and August 2009 in the Chukchi Borderland (46 ng m -2 d -1 and 33 ng m -2 d -1 , respectively) [37]. This is not surprising given that generally shallow Arctic shelves are more productive than the basin and slope regions [11,14].…”
Section: Seasonal Variations Of Hbi and Diatom Export In The Northeasmentioning
confidence: 72%
See 2 more Smart Citations
“…Peak IP 25 fluxes during early July 2016 (1331 ng m -2 d -1 ), coincided with the largest flux of the diatom group Gyrosigma/Pleurosigma/Haslea (Fig 2D), which account for~1% of the relative abundance of major diatom taxa groups [49]. This value is higher than maximum values observed in August 2008 and August 2009 in the Chukchi Borderland (46 ng m -2 d -1 and 33 ng m -2 d -1 , respectively) [37]. This is not surprising given that generally shallow Arctic shelves are more productive than the basin and slope regions [11,14].…”
Section: Seasonal Variations Of Hbi and Diatom Export In The Northeasmentioning
confidence: 72%
“…The largest concentration observed (12 μg g -1 TOC), in addition to samples with values exceeding 10 μg g -1 TOC (n = 4), suggest there were localized areas of elevated ice algal export in the Pacific Arctic. One prior study of IP 25 in the Pacific Arctic indicated comparable concentrations (0-5 μg g -1 TOC [37]). However, direct comparisons with our data may be equivocal because of the less productive location further offshore near the Chukchi Borderlands.…”
Section: Latitudinal Gradients Of Sympagic Hbis and Declining Sea Icementioning
confidence: 90%
See 1 more Smart Citation
“…Figure 4(B); c=0.17). Since some recently reported sediment trap data from the Chukchi Sea showed that the epi-brassicasterol flux was still relatively high in late summer, while the HBI III flux was reduced in summer compared to spring values (Bai et al 2019), it follows that certain sterols potentially integrate, to some degree, both spring and summer conditions. Accordingly, the major production of IP 25 in sea ice and HBI III in open waters along the sea ice edge during the spring season appear to provide the most reliable biomarker pair for estimating PIP 25 -derived SpSIC in the Chukchi Sea, while the additional use of P B IP 25 may potentially provide complementary insights into subsequent summer sea ice trends.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term sediment traps have been deployed to monitor POC fluxes in areas of the western Arctic Ocean, such as the Laptev Sea, Beaufort Sea, Chukchi Sea, and Canada Basin (O'Brien et al, 2006;Fahl and Nöthig, 2007;Forest et al, 2007;Hwang et al, 2008;Lalande et al, 2009aLalande et al, ,b, 2020Honjo et al, 2010;Watanabe et al, 2014;Miquel et al, 2015;Bai et al, 2019). In the Laptev Sea, where sea ice has decreased by 40% over 20 years, the continuous decrease in sea ice has enhanced POC export, potentially altering the structure of the marine ecosystem (Lalande et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%